Determinan Perilaku Pola Makan Vegetarian pada Orang Dewasa Berdasarkan Pendekatan Theory of Planned Behavior - Syamsul Bahri; Muhammad Azwar; Faradiba Anggraeni (LPPM STIKES Marendeng Majene, 2026)
A vegetarian diet is a plant-based dietary behavior increasingly recognized as a strategy to support the prevention of non-communicable diseases. However, maintaining vegetarian dietary practices is influenced not only by nutritional factors but also by psychosocial determinants. This study aimed to analyze determinants of vegetarian dietary behavior among adults using the Theory of Planned Behavior approach. An analytical observational study with a cross-sectional design was conducted among 115 adult vegetarians in the Ajatappareng region, South Sulawesi, selected through purposive sampling. Independent variables included attitude, subjective norm, perceived behavioral control, and intention, while the dependent variable was vegetarian dietary behavior. Data were analyzed using chi-square tests and multiple logistic regression. Bivariate analysis showed that attitude (p=0.003), subjective norm (p=0.018), perceived behavioral control (p<0.001), and intention (p<0.001) were significantly associated with vegetarian dietary behavior. After multivariate adjustment, positive attitude (AOR=2.27; 95% CI:1.02–5.05), high perceived behavioral control (AOR=3.25; 95% CI:1.32–8.00), and strong intention (AOR=4.81; 95% CI:1.89–12.25) remained significant determinants. Intention was the strongest predictor of healthy vegetarian dietary behavior. These findings suggest that health promotion interventions should move beyond providing nutritional information by fostering intrinsic motivation, emotional engagement, and self-regulatory capacity to support sustained adherence to plant-based dietary practices.